2021
DOI: 10.15376/biores.16.1.1875-1890
|View full text |Cite
|
Sign up to set email alerts
|

Performance properties of particleboard panels modified with nanocellulose/boric acid

Abstract: The physical and mechanical properties of particleboard panels were evaluated relative to various loading levels of nanocellulose (NC) and boric acid (BA) in the urea-formaldehyde (UF) resin used for panel production. The results showed that NC and BA reinforcement substantially affected the performance properties of the particleboard panels. It was determined that using 3% NC and 3% BA in the panels afforded the best results relative to thickness swelling (TS), water absorption (WA), moisture content (MC), mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Therefore, PB contributes to a beneficial cycle of resource use, and both its economic importance and production are experiencing continuous growth. Diversification of the raw materials and adhesives used in PB has been investigated to improve its performance (García-Ortuño et al 2011;Altgen et al 2015;Cui et al 2015;Wang et al 2017;Yildirim and Candan 2021;Kuqo et al 2023). Moreover, PB applications have been expanded to structural implementations; for example, structural PB (SPB) has been used to wall, floor, and roof for light-frame wood houses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PB contributes to a beneficial cycle of resource use, and both its economic importance and production are experiencing continuous growth. Diversification of the raw materials and adhesives used in PB has been investigated to improve its performance (García-Ortuño et al 2011;Altgen et al 2015;Cui et al 2015;Wang et al 2017;Yildirim and Candan 2021;Kuqo et al 2023). Moreover, PB applications have been expanded to structural implementations; for example, structural PB (SPB) has been used to wall, floor, and roof for light-frame wood houses.…”
Section: Introductionmentioning
confidence: 99%
“…Boron compounds are widely used as flame retardants in wood and bamboo products, which considerably reduces the severity of thermal degradation (Nagieb et al 2011;Wu and Xu 2014;Cavdar et al 2015). In addition to imparting flame retardancy, boron compounds also have several advantages in wood preservation, and are especially effective against fungi and termites (Nagieb et al 2011;Yildirim and Candan 2021). As one of the most widely used boron compounds, boric acid is a good preservative and flame retardant for biomaterials (Pedieu et al 2012;Efhamisisi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most widely used boron compounds, boric acid is a good preservative and flame retardant for biomaterials (Pedieu et al 2012;Efhamisisi et al 2016). In addition, the thermal stability of nanocellulose and lignocellulose, which are used in bio-composites, could also be improved by boric acid modification (Zhang et al 2020;Yildirim and Candan 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The use of UF and PF resins as wood adhesives has several advantages which have been mentioned in previous studies (Younesi-Kordkheili and Pizzi 2020a; Younesi-Kordkheili and Pizzi 2020b; Younesi-Kordkheili and Pizzi 2021). However, the panels produced with these types of adhesives cause carcinogenic formaldehyde emissions, which are known to have negative effects on human health in their service life and it is the greatest drawback of these adhesives (Conner 1996; Dunky 1997; Gonultas 2018; Yildirim et al 2021; Yildirim and Candan 2021). Yildirim et al (2021) and Yildirim and Candan (2021) indicated that the chemical performance properties of UF resin could be enhanced by using proper nanocellulose, boric acid and borax loading levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, the panels produced with these types of adhesives cause carcinogenic formaldehyde emissions, which are known to have negative effects on human health in their service life and it is the greatest drawback of these adhesives (Conner 1996; Dunky 1997; Gonultas 2018; Yildirim et al 2021; Yildirim and Candan 2021). Yildirim et al (2021) and Yildirim and Candan (2021) indicated that the chemical performance properties of UF resin could be enhanced by using proper nanocellulose, boric acid and borax loading levels. In recent years, many research works have been carried out to replace synthetic adhesives with natural macromolecules obtained from natural resources such as lignin and corn flour.…”
Section: Introductionmentioning
confidence: 99%